2020
DOI: 10.1108/ijoa-03-2020-2066
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction in the context of public–private partnerships

Abstract: Purpose This study aims to provide insights into the public–private partnerships (PPP) concept and its performance measurement in the health-care sector, identifying and refining critical success factors, including the perceived quality of health care, as evidenced by patient satisfaction and policy requirements for successful PPP implementation. Design/methodology/approach This theoretical study explores the existing literature on the relationship between service quality and patient satisfaction, to propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 166 publications
(170 reference statements)
0
16
0
2
Order By: Relevance
“…Di sisi lain, Mengoptimalkan kepuasan pasien dalam pelayanan kesehatan memiliki banyak manfaat. Telah dibuktikan secara empiris bahwa pasien yang puas memiliki tingkat penerimaan serta kepatuhan yang lebih baik terhadap perawatan dan pengobatan dan dengan demikian secara keseluruhan meningkatkan hasil kesehatan (Mallat et al, 2020;Ullah et al, 2020).…”
Section: Pendahuluanunclassified
“…Di sisi lain, Mengoptimalkan kepuasan pasien dalam pelayanan kesehatan memiliki banyak manfaat. Telah dibuktikan secara empiris bahwa pasien yang puas memiliki tingkat penerimaan serta kepatuhan yang lebih baik terhadap perawatan dan pengobatan dan dengan demikian secara keseluruhan meningkatkan hasil kesehatan (Mallat et al, 2020;Ullah et al, 2020).…”
Section: Pendahuluanunclassified
“…The service quality factor is a factor of trust that has received increasing attention from research ers and those interested in the health and medical care sector in various countries, for more than a decade and continues to represent the compass and the central issue of concern to medical service providers in general. with the growing medical awareness among patients and their constant pursuit of high-quality medical services continuously, the similar nature of the provision of medical services in all its forms has become the standard through which you can distinguish and differentiate between the service provider is the quality in a highly competitive marketing environment in this vital sector to ensure survival and success [41]. Service quality has been defined as the degree to which a medical provider can meet patient expectations [42].…”
Section: Service Qualitymentioning
confidence: 99%
“…Patient satisfaction is well-established and principal in the marketing of medical services of medical or health services, receiving wide attention from researchers and service providers alike, to identify its contents, exact details, and effects on various medical care joints in general [41]. By looking at the literature on the concept of patient satisfaction, it was noted that there is no common definition agreed upon, as it was defined as a state of pleasure or happiness that the patient realizes or feels during the provision of medical service, a practical guide to its effectiveness [53].…”
Section: Patients Satisfactionmentioning
confidence: 99%
“…6,92 Such interactions between public and private players assist in improving the capacity and sustainability of a health care system. 93,94 Vecchi and Cusumano 95 discussed various types of public-private partnership models in health care. Kaya et al 96 suggested some contracting mechanisms for public and private collaboration to evolve a more balanced health system.…”
Section: Public-private Partnershipmentioning
confidence: 99%
“…A public‐private partnership in health can ensure effective and efficient health care delivery by upgrading the quality and scope of public health services 6,92 . Such interactions between public and private players assist in improving the capacity and sustainability of a health care system 93,94 …”
Section: Literature Reviewmentioning
confidence: 99%